Livestock-associated methicillin-resistant Staphylococcus aureus epidemiology, genetic diversity, and clinical characteristics in an urban region - Konstantinovski, Maria M.; Schouls, Leo M.; Witteveen, Sandra; Claas, Eric C. J.; Kraakman, Margriet E.; Kalpoe, Jayant; Mattson, Eva; Hetem, David J.; van Elzakker, Erika P. M.; Kerremans, Jos; Hira, Vishal; Bosch, Thijs; et al. (Frontiers in Microbiology, 2022)
Objectives While livestock-associated MRSA (LA-MRSA), defined as CC398, is a well-known pathogen among those working with livestock, there are indications that LA-MRSA prevalence among the general population is increasing. However, the clinical impact in urban areas remains unknown. The aim of this study was to assess the genetic epidemiology and clinical characteristics of LA-MRSA in an urban area with a limited livestock population. Methods In this retrospective study, we evaluated LA-MRSA strains that were collected between 2014 and 2018 from patients who received clinical care in a single urban area in the Netherlands. Patient files were assessed for livestock exposure data, clinical findings and contact tracing information. Next-generation sequencing (NGS) analysis in combination with wgMLST was conducted to assess genetic diversity, relatedness and to detect virulence and resistance genes. Results LA-MRSA strains were cultured from 81 patients, comprising 12% of all the MRSA strains found in seven study laboratories between 2014 and 2018. No livestock link was found in 76% of patients (n=61), and 28% of patients (n=23) had an infection, mostly of the skin or soft tissue. Contact tracing had been initiated in 14 cases, leading to the identification of 2 hospital transmissions: a cluster of 9 cases and one of 2 cases. NGS data were available for 91% (n=75) of the patients. wgMLST confirmed the clusters detected via contact tracing (n=2) and identified 5 additional clusters without a known epidemiological link. Relevant resistance and virulence findings included the PVL virulence gene (3 isolates) and tetracycline resistance (79 isolates). Conclusions LA-MRSA may cause a relevant burden of disease in urban areas. Surprisingly, most infections in the present study occurred in the absence of a livestock link, suggesting inter-human transmission. These findings and the presence of PVL and other immune evasive complex virulence genes warrant future surveillance and preventative measures.